Genetic divergence analysis of lime - Rahman, MM; Al Munsur, MAZ (Journal of the Bangladesh Agricultural University, 2010)
Genetic divergence of 40 lime accessions was estimated using D2 and principal component analysis. The genotypes under study fell into 6 clusters. The distribution pattern indicated that the maximum number of genotypes were included in cluster III and the minimum number in cluster VI. The inter cluster distance in most of the cases were higher than the intra cluster distance indicating wider genetic diversity among the accessions of different groups. The highest inter cluster distance was observed between cluster II and III (1568.51) followed by cluster II and VI (1223.72) showing wide diversity among the groups. The highest intra-cluster distance was observed for the cluster III and the lowest for the cluster VI. Leaf area and number of stamen showed maximum contribution towards total divergence among the genotypes. Keywords: Genetic Divergence; Lime; PCA; Genetic diversity DOI: 10.3329/jbau.v7i1.4795 J. Bangladesh Agril. Univ. 7(1): 33-37, 2009